The relationship between articulatory control and improved phonemic accuracy in childhood apraxia of speech: a longitudinal case study. - Grigos MI; Kolenda N (Clinical Linguistics & Phonetics, 2010)
Jaw movement patterns were examined longitudinally in a 3-year-old male with childhood apraxia of speech (CAS) and compared with a typically developing control group. The child with CAS was followed for 8 months, until he began accurately and consistently producing the bilabial phonemes /p/, /b/, and /m/. A movement tracking system was used to study jaw duration, displacement, velocity, and stability. A transcription analysis determined the percentage of phoneme errors and consistency. Results showed phoneme-specific changes which included increases in jaw velocity and stability over time, as well as decreases in duration. Kinematic parameters became more similar to patterns seen in the controls during final sessions where tokens were produced most accurately and consistently. Closing velocity and stability, however, were the only measures to fall within a 95% confidence interval established for the controls across all three target phonemes. These findings suggest that motor processes may differ between children with CAS and their typically developing peers.